Maternal aging affects life performance of progeny in a Holstein dairy cow model. (1st August 2014) - Astiz, S.; Gonzalez-Bulnes, A.; Sebastian, F.; Fargas, O.; Cano, I.; Cuesta, P.
<x content-type="archive" xml:space="preserve">Abstract</x> The development and life performance of 404 high-producing Holstein dairy cows was studied from birth onwards and during two lactations. The management, environment and parental genetics of the cows were known in detail. Cluster analysis identified four performance 'types': high-yielding (HY) cows and persistently high-yielding (PHY) cows, which accounted for 33% of the animals; medium-yielding (MY) cows, 41%; and low-yielding (LY) cows, 26%. Prenatal determinants of the life performance of the progeny were analyzed. Developmental and environmental factors were excluded as determinants of performance (including birth weight, level of passive immunity transfer, growth rate, age at first parturition and reproductive efficiency). Life performance did show minor seasonal effects, with more HY cows but less PHY being born during the cold season (90.1% in HY; 58.3% in PHY v. 81.5%). Instead, the single most important factor influencing life performance of daughters was maternal age. HY cows were born from the youngest mothers (1.89±1.14 parturitions, 3.12±1.42-year old), whereas LY cows were born from the oldest (2.72±1.80 parturitions, 3.97±2.01-year old; P<0.001). Life performance of the dams did not differ among clusters. In addition, metabolic parameters (fat and protein yield) were found to correlate significantly with yields between the first and second lactations (milk yield: r=0.357; fat yield: r=0.211; protein yield: r=0.277; P<0.0001), suggesting the influence of the individual. These results suggest that under optimal health, nutritional and environmental conditions, maternal aging is an important determinant of the life performance of progeny and argue for the need to identify conditions that contribute to health and disease in progeny according to the Developmental Origin of Health and Disease or DOHaD concept. Our findings may help the development of novel management guidelines for dairy farms.